2019
DOI: 10.1136/tsaco-2018-000257
|View full text |Cite
|
Sign up to set email alerts
|

Rib fractures in the elderly: physiology trumps anatomy

Abstract: IntroductionRib fractures in elderly patients are associated with increased morbidity and mortality. Predicting which patients are at risk for complications is an area of debate. Current models use anatomic, physiologic or laboratory parameters in isolation to answer this question. The ‘RibScore’ is an anatomic model that assesses fracture severity. Given that frailty is a major driver of adverse outcomes in the elderly, we hypothesize that the combined analysis of fracture severity, physiologic reserve and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…In fact, recent studies in patients with chest wall trauma suggest that physiologic parameters and patient reserve are more useful assessment tools than age groups and anatomical descriptions. 17,18 This is also consistent with the more recent realization in geriatric trauma patients that functional status and physiologic reserve, that is, frailty or the lack thereof, are more useful and accurate descriptors of patient risk than many traditional parameters. 19,20 The only adverse consequence of the revised triage guidelinewefoundwasasignificantlyincreasedICUand hospital LOS, though by 1 day only.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In fact, recent studies in patients with chest wall trauma suggest that physiologic parameters and patient reserve are more useful assessment tools than age groups and anatomical descriptions. 17,18 This is also consistent with the more recent realization in geriatric trauma patients that functional status and physiologic reserve, that is, frailty or the lack thereof, are more useful and accurate descriptors of patient risk than many traditional parameters. 19,20 The only adverse consequence of the revised triage guidelinewefoundwasasignificantlyincreasedICUand hospital LOS, though by 1 day only.…”
Section: Discussionsupporting
confidence: 78%
“…Despite a substantial proportion of patients with multiple fractured ribs, sternal fractures, scapula fractures, and hemothorax or pneumothorax, the morbidity and mortality of our patient population were lower than traditionally reported 1,[3][4][5]14 but consistent with the results of other, primarily more recent studies that similarly demonstrated improved outcomes. 2,9,18 These changes likely not only reflect the positive impact of advanced critical care and aggressive ICU admission guidelines but also the widespread use of chest CT scans that have much higher sensitivity for rib fractures than chest X-ray, thus increasing the number of patients with a low number of rib fractures. 2 In our analysis, we excluded patients with severe associated polytrauma that would have mandated ICU admission for these injuries given the study focus on improving rib fracture triage and ICU admission guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of a scoring system that is easily standardized across institutions should not be understated, but recent literature would suggest that patient physiological status may play a more integral role in predicting adverse outcomes. 13,23 The sequential clinical assessment of respiratory function score described by Hardin et al 13 in 2019 is similar to the current study's CPG in that it relies on serial patient assessments rather than only the admission assessment, and it uses FVC as one of the measured parameters. Performing admission and serial assessments allows care teams to appropriately triage patients at admission and identify changes in physiologic status in a timely manner.…”
Section: Discussionmentioning
confidence: 84%
“…Consideration of frailty, social circumstances and co-morbidities should now have as equal emphasis as age and injury severity when discharging patients directly home from the ED [27][28][29]. A recent study found that in addition to the anatomic features that compose the RibScore, frailty is a significant risk factor for predicting pulmonary complications in this patient population [27]. These variables should therefore be considered for inclusion in risk prediction tools and pathways and patient advice sheets.…”
Section: Discussionmentioning
confidence: 99%